Spotlight on Cloud : Cybersecurity, Privacy, and GDPR with Bill Mew - Mew, Bill (O'Reilly Media, Inc., 2020)
Cyberattacks and breaches are at an all-time high, and the threat of cybersecurity litigation is rising dramatically. But many organizations are still inadequately prepared. The future of technology will depend upon erecting meaningful protections and reducing risk for your users in order to maximize your products' social and economic value. However, for this to happen, a number of key issues must be addressed. In this Spotlight on Cloud , expert Bill Mew discusses four systemic cybersecurity and privacy issues, and addresses how to prepare for a worst-case scenario. Recorded on October 3, 2019. See the original event page for resources for further learning or watch recordings of other past events . O'Reilly Spotlight explores emerging business and technology topics and ideas through a series of one-hour interactive events. In live conversations, participants share their questions and ideas while hearing the experts' unique perspectives, insights, fears, and predictions for the future. In every edition of Spotlight on Cloud , you'll learn about the complex, ever-evolving world of the cloud. You'll discover how successful companies have adopted and embraced this massive network of shared information and how you can follow their lead to transform your organization and prepare for the Next Economy.